Myopia - Baird, Paul N.; Saw, Seang-Mei; Lanca, Carla; Guggenheim, Jeremy A.; Smith III, Earl L.; Zhou, Xiangtian; Matsui, Kyoko-Ohno; Wu, Pei-Chang; Sankaridurg, Padmaja; Chia, Audrey; Rosman, Mohamad; Lamoureux, Ecosse L.; et al. (Nature reviews. Disease primers, 2020)
Myopia, also known as short-sightedness or near-sightedness, is a very common condition that typically starts in childhood. Severe forms of myopia (pathologic myopia) are associated with a risk of other associated ophthalmic problems. This disorder affects all populations and is reaching epidemic proportions in East Asia, although there are differences in prevalence between countries. Myopia is caused by both environmental and genetic risk factors. A range of myopia management and control strategies are available that can treat this condition, but it is clear that understanding the factors involved in delaying myopia onset and slowing its progression will be key to reducing the rapid rise in its global prevalence. To achieve this goal, improved data collection using wearable technology, in combination with collection and assessment of data on demographic, genetic and environmental risk factors and with artificial intelligence are needed. Improved public health strategies focusing on early detection or prevention combined with additional effective therapeutic interventions to limit myopia progression are also needed. This Primer by Baird, He and colleagues reviews the epidemiology, pathophysiology, diagnosis and treatment of myopia, a prevalent eye disorder among school-aged children that affects distance vision and may result in irreversible visual impairment.